A new method of hybrid optimization of small cell range development and density for energy efficient ultra‐dense networks. Issue 7 (16th March 2022) - Sidiq, Sumina; Sheikh, Javaid A.; Mustafa, Farhana; Malik, Bilal A.
Abstract: Ultra‐dense networks (UDNs) which comprise of small and macro cells, are considered the principal solution for increasing demands of data. However, making energy efficient networks will be a challenge for researchers. In this article, a hybrid optimization technique is proposed to enhance the energy efficiency (EE) of the UDNs, considering the user correlation and hybrid optimization of the density and transmitting power of the small‐cell‐base‐station (SBS). More precisely, the problem framed is a problem of convex‐linear programming and hence is divided into two sub‐problems: cell correlation and hybrid optimization. The expression for the EE of the system is derived in the closed‐form as a factor of the density of SBSs and small cell‐range‐development (CRD) bias dependent on the Poisson point process (PPP) followed by the sequential‐search‐algorithm to improve the small CRD bias and SBS density correspondingly. Additionally, to realize hybrid optimization of the small CRD bias and density of SBSs, a heuristic algorithm is put forward to accomplish the EE of the system. It is revealed from the simulation outcomes that the proposed small CRD bias and SBS density hybrid optimization significantly enhances the EE of the system with low computational intricacy. Abstract : This figure represents the graphical abstract of the proposed work. Energy efficiency of the UDN networks are achieved by using hybrid optimization technique. The problem is formulated as convex linear problem. The closed form as a factor has been considered as a factor of the density of SBSs. After this the Poisson point process and heuristic algorithms are finally formulated and analyzed to achieve energy aware networks.